Electrochemical and spectroelectrochemical properties of thiadiazole substituted metallo-phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
4-Thiadiazole substituted phthalonitrile and peripherally tetra-substituted phthalocyanine Cu(II), Fe(II) and Ti(IV)O complexes have been synthesized for the first time. Electrochemical properties of these complexes were determined with voltammetric and in situ spectroelectrochemical measurements. CuPc has redox inactive Cu2+ center, therefore it gave three Pc based reduction and two Pc based oxidation processes. TiOPc and FePc complexes gave metal based redox processes in addition to Pc based redox reactions due to the redox activity of Ti4+O and Fe2+ metal centers. Although FePc also gave three reduction and two oxidation reactions, peak potentials of these processes are different than those of CuPc due to the different assignments of the redox reactions. TiOPc went to five reduction and one oxidation reactions. Assignments of the redox processes were carried out with in situ spectroelectrochemical measurements. Spectra and color of the electrogenerated redox species of the complexes were also determined with in situ spectroelectrochemical and in situ electrocolorimetric measurements. Distinct color differences between the electrogenerated redox species were observed, which indicated their possible electrochromic usages. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Thiadiazole; Phthalocyanine; Metallophthalocyanine; Electrochemistry; Spectroelectrochemistry; IRON(II) PHTHALOCYANINE; TITANYL PHTHALOCYANINES; FUNCTIONALIZED GRAPHENE; COPPER; COMPLEXES; METALLOPHTHALOCYANINES; TITANIUM(IV); MOIETIES; BEHAVIOR; ZINC